2006
DOI: 10.1177/1045389x06061129
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-mechanical Model for Actuation Based on Biological Membranes*

Abstract: Plants have the ability to develop large mechanical force from chemical energy available with bio-fuels. The energy released by adenosine tri-phosphate (ATP) hydrolysis assists the transport of ions and fluids to achieve volumetric expansion and homeostasis. Materials that develop pressure and hence strain similar to bio-materials are classified as nastic materials. Recent calculations for controlled actuation of an active material inspired by biological transport mechanism demonstrated the feasibility of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…Although appearing as a promising candidate for morphing skins, the research in this area is not extensive. Other materials that have attracted research interest in this field include the Veriflex ® -based polymer [61], which is thermally activated, and the nastic shape changing materials [62]. The nastic materials refer to a class of substances that mimic biological systems to produce large deformations through the conversion of chemical energy available within the material.…”
Section: Morphing Skinsmentioning
confidence: 99%
“…Although appearing as a promising candidate for morphing skins, the research in this area is not extensive. Other materials that have attracted research interest in this field include the Veriflex ® -based polymer [61], which is thermally activated, and the nastic shape changing materials [62]. The nastic materials refer to a class of substances that mimic biological systems to produce large deformations through the conversion of chemical energy available within the material.…”
Section: Morphing Skinsmentioning
confidence: 99%
“…The fundamental model used in the current research can be found in the work given by Homison and Weiland (2006). (Sundaresan and Leo, 2006a).…”
Section: Model Description Ion Transport Modelmentioning
confidence: 99%
“…I NSPIRED by the nastic movements in the plants kingdom, for example, the Venus Flytrap, the artificial nastic materials, which allow for significant deformation through the mechanism of controlled charge and fluid across the cell membrane, have been utilized in the design of advanced actuators in recent years. These materials can generate large mechanical force through the conversion of chemical energy stored in biofuels with actuation energy density on the order of 100 kJ/m 3 (Sundaresan and Leo, 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biologically inspired design has offered many intriguing systems that draw inspiration from natural systems ranging from the simple venus fly trap [1] to flying snakes [2]. These approaches aim to recreate various desired phenomena that are exhibited in nature through careful tailoring of system properties to best match the natural solution.…”
Section: Introductionmentioning
confidence: 99%